Efektivitas Penerapan PPN 11 Bagi Pelaku UMKM Di Kecamatan Pamulang, Tangerang Selatan - Darul Fahmi; Rahman Faisal (Prisani Cendekia, 2023)
The UU HPP was officially enacted on October 7, 2021, by the government and the People's Representative Council. It was published as Law Number 7 of 2021 on October 29, 2021 (Online Pajak, 2021). The main objective of the UU HPP is to support the accelerated recovery of the economy post-Covid-19 and promote economic growth (Ministry of Finance of the Republic of Indonesia, 2021). The significant impact of the pandemic is evident in the Indonesian economy. Micro, small, and cooperative businesses have been heavily affected by the Covid-19 outbreak. Sales have declined, capital has diminished, orders have decreased, raw material supply has become difficult, and loan defaults have occurred. Technology becomes a vital element in transforming conventional industries into digital ones, facilitating the transfer of data without human intervention and utilizing big data to determine business direction. The objective of this research is to investigate the effectiveness of the implementation of a 11% Value Added Tax (VAT) for Micro, Small, and Medium Enterprises (MSMEs) in the Pamulang District. Data collection for this study will be conducted through observation, interviews, and documentation.